Reformulating the Institutionalization and Enforcement of General and Regional Head Election Campaign Fund Reports - Muhammad Machshush Bil Izzi; Fani Rahmah Latifah; Nurul Febria Rizwani (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
Campaign Funds are a vital instrument for the realization of Campaign activities by General and Regional Head Election Participants. However, several problems occurred in the Campaign Fund report such as the practice of realizing the use or expenditure of Campaign Funds that were not in accordance with the report submitted to the General Election Commission, the formality of the Campaign Fund report and the disparity in the imposition of sanctions, as well as the inconsistency of law enforcement on the Campaign Fund report. Various previous studies have discussed the problems and importance of transparency in Campaign Fund reporting. However, the issue of institutional reformulation and alternative enforcement of Campaign Fund reports is still minimally highlighted. Based on this, this study focuses on the reformulation the institutionalization and enforcement of Campaign Fund reporting in General and Regional Head Elections. In this study, the methodology used to analyze the problem is using a normative juridical methodology. This study found that it is necessary to reformulate the arrangements institutionalization and enforcement of Campaign Fund reports to strengthen substantive Campaign Fund reports, including by involving Financial Transaction Reporting and AnalysisCenter in the supervision and enforcement mechanism of Campaign Funds that are unreasonable or illegal, so that they are not just administratively compliant or noncompliant with the Campaign Fund reports.